(untitled) (Research, Society and Development, 2020)
The insertion of undergraduate students in the school environment is an important practice for future teacher’s improvement, enabling experiences within the school: this is the proposal of “Programa Residência Pedagógica” (PRP). The PRP is a teacher training policy proposed by the “Coordenação de Aperfeiçoamento de Pessoal de Nível Superior” (CAPES) together with the Ministry of Education (MEC) and is implemented and organized by teachers of undergraduate degrees, teachers of public schools, students of undergraduate degrees and several other agents. Since 2018, beginning of the program, until the beginning of 2019, undergraduate students belonging to the PRP have been immersed within schools, experiencing their future work environment, the dynamics of the school, its curriculum and the whole system that transforms the school into what it is. This work intends to describe the result of the experiences of a group of PRP students during stage II of the PRP, the setting, in one of the schools participating in the program and its main objective is to discuss the results of the residents’ setting in the school environment and how this influenced their teaching practice. With the setting, the students had the possibility to get to know the school reality better and developed a feeling of belonging regarding the school-field, reinforcing the importance of this stage of the program.